2016
DOI: 10.1097/ncq.0000000000000131
|View full text |Cite
|
Sign up to set email alerts
|

Just-in-Time Training for High-Risk Low-Volume Therapies

Abstract: High-risk low-volume therapies are those therapies that are practiced infrequently and yet carry an increased risk to patients because of their complexity. Staff nurses are required to competently manage these therapies to treat patients' unique needs and optimize outcomes; however, maintaining competence is challenging. This article describes implementation of Just-in-Time Training, which requires validation of minimum competency of bedside nurses managing high-risk low-volume therapies through direct observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“… 23 26 This methodology has also been utilized to enhance nursing and resident education and system-wide QI education to improve retention and engagement. 27 30 The use of this methodology in our project may have contributed to the performance improvements with anthropometry measurements in the PICU.…”
Section: Discussionmentioning
confidence: 99%
“… 23 26 This methodology has also been utilized to enhance nursing and resident education and system-wide QI education to improve retention and engagement. 27 30 The use of this methodology in our project may have contributed to the performance improvements with anthropometry measurements in the PICU.…”
Section: Discussionmentioning
confidence: 99%
“…It also can be employed to focus on teamwork and communication by allowing an analysis of team behaviors. The scenario can be employed as just-in-time training for teams when a meningomyelocele delivery is anticipated and practice is desired prior to the actual delivery [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, JiT training strategy was found to markedly improve knowledge of nursing training staff that brought prior JiT training information to the bedside educational discussions (13). JiT training tool was used to validate minimum competency of bedside nursing staff managing high-risk low-volume therapies in order to ensure patient safety (14). A recent literature report also suggested that JiT active learning of evidence-based healthcare curricula created an opportunity for students to engage with facilitators and peers, enhance knowledge-based skills, and increase their chances of reinforcing and retaining their curricular knowledge (15).…”
Section: Introductionmentioning
confidence: 99%